P3-071Immune checkpoint inhibitor for advanced or recurrent non-small cell lung cancer patients with poor performance status. (7th October 2019) - Koyama, Junji; Kimura, Tomoki; Oi, Hajime; Yamano, Yasuhiko; Yokoyama, Toshiki; Matsuda, Toshiaki; Kataoka, Kensuke; Matsuzawa, Reiko; Fukihara, Jun; Sakamoto, Koji; Morise, Masahiro; Hashimoto, Naozumi; et al.
Abstract: Background: The efficacy and safety of immune checkpoint inhibitor (ICI) for advanced or recurrent non-small cell lung cancer (NSCLC) with poor performance status (PS) is unknown. Methods: A multicenter retrospective study was conducted for patients with advanced or recurrent NSCLC with PS ≥ 2 who received ICI between January 2016 and September 2018. The objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and occurrence of immune-related adverse event (irAE) were assessed for all participants. Results: A total of 20 patients (median age: 61 years; age range: 44-80 years; male/female ratio: 10/10) were included with the following demographics: PS2/3: 14/6; current or former/never smoker ratio: 15/5; squamous/non-squamous cell carcinoma cases: 2/18; PD-L1 ≥50%/1%-49%/0%/unknown: 6/2/1/11; nivolumab/pembrolizumab/atezolizumab: 11/5/4; 1 st /2 nd /3 rd or subsequent line: 5/4/11. For the overall population, ORR, DCR, median PFS, and median OS were 5%, 20%, 0.8 months [95% confidence interval (CI), 0.5-1.8], and 2.5 months (95% CI, 1.3-4.3), respectively. Even for the population with PD-L1 ≥50%, ORR, DCR, median PFS, and median OS were 0%, 17%, 0.9 months (95% CI, 0.2-NA), and 3.2 months (95% CI, 0.8-NA), respectively. IrAE was recorded in 5 cases; the most common being fever (n = 2) and included pruritus, cholangitis, and pneumonitis (n = 1 each). In the case with cholangitis, ICI was discontinued due to irAE. Conclusion: The efficacy of ICI for advanced or recurrent NSCLC patients with PS ≥ 2 was suggested to be poor, including the participant population with PD-L1 ≥ 50%.